2004
DOI: 10.1590/s0102-76382004000100008
|View full text |Cite
|
Sign up to set email alerts
|

Acesso minimamente invasivo para troca da valva aórtica: resultados operatórios imediatos comparativos com a técnica tradicional

Abstract: Objective: Minimally invasive heart surgeries are approaches used to reduce trauma, to give better cosmetic results and to reduce hospital costs with the same safety as conventional surgery. This study was designed to compare the operative results from patients who underwent minimally invasive aortic valve replacement with those who were submitted to the standard procedure.Method: The operative and immediate postoperative results of 12 consecutive patients who received minimally invasive isolated aortic valve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In this cases series, CPB was used in a conventional manner and was not vacuum-assisted since the cannulation was transthoracic occupying the same surgical field. This surgical option required larger chest incisions, reducing the aesthetic benefit and the expected reduction of postoperative discomfort [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In this cases series, CPB was used in a conventional manner and was not vacuum-assisted since the cannulation was transthoracic occupying the same surgical field. This surgical option required larger chest incisions, reducing the aesthetic benefit and the expected reduction of postoperative discomfort [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies did not show significant differences for these parameters between MIS and sternotomy [ 4 , 9 , 10 , 20 ] . In accordance with the literature, in our study we also found a tendency for shorter time of stay in the ICU and hospital stay for the MIS approach, although not statistically significant, possibly due to the number of patients evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Among 14 studies comparing the length of stay in the ICU and length of hospital stay, 10 of them concluded that the MIS approach decreased the length of hospital stay [ 3 , 5 , 6 , 11 , 12 , 14 , 16 , 18 , 22 ] , and among these 7 studies also showed shorter length of stay in the ICU [ 10 , 14 , 16 - 18 , 23 , 24 ] . Four studies did not show significant differences for these parameters between MIS and sternotomy [ 4 , 9 , 10 , 20 ] . In accordance with the literature, in our study we also found a tendency for shorter time of stay in the ICU and hospital stay for the MIS approach, although not statistically significant, possibly due to the number of patients evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation